PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Afifah Aulina; Saksono Budi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Capital Structure proxied by using DER (Debt to Equity Ratio) and Company Size proxied by using SIZE on Financial Performance proxied by using ROA (Return On Asset) in Telecommunication Sector Companies Listed on the Indonesia Stock Exchange used Library Research with analysis techniques using statistics with classical testing, regression, determination and hypothesis testing. The results of this study indicate that (1) Capital structure simultaneously has a positive and significant effect on financial performance, (2) Company size simultaneously has a negative and significant effect on financial performance, (3) Capital structure and company size simultaneously have a positive and significant effect on financial performance.